The Use of Project-Based Digital Comics on Social Science Content to Improve Learning Outcomes Students of 5th Grade Elementary School Students - Ni Kadek Yuwika Ulandari; I. W. Sujana (Journal for Lesson and Learning Studies, 2022)
The minimal variety of media used and learning activities that are still teacher-centered prevent student learning outcomes from declining. This study aimed to create teaching media in the form of digital comics based on social studies content projects for fifth-grade elementary school students. This type of research is a development by adapting the ADDIE model. The subjects in this study were experts consisting of one design expert, one material expert, one design expert, one media expert, and two instrument experts. In comparison, the students consisted of three individual test students, nine small group test students, and 24 effectiveness test students. The data analysis technique used is descriptive quantitative and inferential analysis. Data were obtained by using interviews, questionnaires, and tests. The results of this study were that learning material experts scored 91.66% (very good), design experts 90.00% (very good), and media experts 87.50% (good). The results of the individual trials were 82.50% (good), and the small group trials were 80.83% (good). The results of the t-test found that this project-based digital comic effectively increased the learning outcomes of fifth-grade elementary school students in social studies material. It was concluded that learning media in project-based digital comics is appropriate for the learning process. This research implies the need for project-based comic learning media in learning activities to increase student interest and learning outcomes.